2009
DOI: 10.3747/co.v16i4.355
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Extended-Volume External-Beam Radiation Therapy in High-Risk Esophageal Cancer Patients: A Prospective Experience

Abstract: Background and PurposeExtended-volume external-beam radiation therapy (rt) following esophagectomy is controversial. The present prospective study evaluates the feasibility of extended-volume rt treatment in high-risk esophagectomy patients with a cervical anastomosis receiving postoperative combined chemoradiation therapy.Patients and MethodsFrom 2001 to 2006, 15 patients with resected esophageal cancer were prospectively accrued to this pilot study to evaluate the adverse effects of extended-volume rt. Posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…However, it is not possible to ascertain the significance of this observation from our small, retrospective cohort. We note that grade 5 toxicity was not observed in our previously reported series using 3DCRT [15]. Given the similarity of surgical techniques between our current cohort and our previously reported series, and given the radiobiological similarity between our current and previous dose-fractionation regimes, at the very least we expect IMRT-SIB to be comparable in terms of acute and late toxicity to our previous technique, with comparable survival.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, it is not possible to ascertain the significance of this observation from our small, retrospective cohort. We note that grade 5 toxicity was not observed in our previously reported series using 3DCRT [15]. Given the similarity of surgical techniques between our current cohort and our previously reported series, and given the radiobiological similarity between our current and previous dose-fractionation regimes, at the very least we expect IMRT-SIB to be comparable in terms of acute and late toxicity to our previous technique, with comparable survival.…”
Section: Discussionsupporting
confidence: 67%
“…Our original retrospective study suggested an OS benefit to adjuvant chemoRT over surgery alone, with median overall survival (OS) being extended to 47.5 months with adjuvant chemoRT versus 14.1 months without (p = 0.001) [9]. Irradiation of the anastomosis was associated with a significant improvement in local and regional relapse [10] and reduced recurrence at the anastomotic site [15], implying the importance of local control as a determinant of outcome [16]. Similar benefits of adjuvant chemoRT have been recognized by other authors [17-19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the postoperative target volume is different from that of non-operative radiotherapy. Many target plans have been used in past decades (16,(17)(18)(19)(20)(21), without a standard criterion.…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 43 45 Such extensive fields can effectively lower the chance of local recurrence within the range of radiation portals. 23 Although several studies have demonstrated the safety and feasibility of extended-volume RT, 46 such an extensive irradiation field frequently causes severe gastrointestinal and systemic reactions, and many patients who have poor tolerance are required to suspend the treatment or reduce the radiation dose. Some patients even experience severe radiation-induced fibrosis of the lung, noncancerous pericardial and pleural effusions, and alimentary tract hemorrhages.…”
Section: Current Situation Regarding Port Clinical Target Volume Delimentioning
confidence: 99%